Towards nearly zero-energy educational buildings with the implementation of the Energy Performance of Buildings Directive via energy rehabilitation in cold Mediterranean zones: The case of Spain - Luis M. López-Ochoa; David Bobadilla-Martínez; Jesús Las-Heras-Casas; Luis M. López-González (Energy Reports, 2019)
The European Union, through the Energy Performance of Buildings Directive~and the~Energy~Efficiency Directive, has been establishing requirements and expectations regarding energy savings and efficiency in buildings. The objective of~this study~is to explore energy rehabilitation solutions for educational buildings of the~1980s in cold climate zones of Spain by applying the corresponding adaptation of the European legislation, which is the Basic Document for Energy Saving of the Technical Building Code. The evolution of regulation is studied using three cases, and 12 proposals for achieving nearly zero-energy educational buildings are studied. The analysis of the results obtained shows how changes in energy and environmental policies affect those buildings. Regarding the baseline building, average reductions of~more than 66% in non-renewable primary energy consumption and of more than 71% in CO2 emissions were observed. Additional reductions of at least 10% in non-renewable primary energy consumption and 8% in CO2 emissions are achieved with the alternatives proposed to achieve nearly zero-energy educational buildings. The knowledge of the sector is deepened with this study, which allows the design of future energy rehabilitation policies and promotes policy changes.
Keywords: 330; CO reduction; Cold Mediterranean zones; Educational buildings; Energy savings; EPBD; Spain